Microalgae biofuels production: A systematic review on socioeconomic prospects of microalgae biofuels and policy implications - Moshood, Taofeeq D.; Nawanir, Gusman; Fatimah, Mahmud (Elsevier, 2021)
There is currently no sustainable reliance on liquid fossil fuels worldwide, which ensures that future fiscal, environmental and social stability requires alternative renewable sources of liquid fuel. In order to satisfy the worldwide demand for liquid fuel, microalgae production is needed on a commodity scale; however, there are significant challenges in ensuring that production is economical and durable. This paper aims to examine microalgae' economic and cost advantages in greater depth and evaluate how vital biofuel policy support is for microalgae. A systematic analysis outlined the obstacles facing traditional biofuels to achieve these targets and proposed microalgae biofuels' economic opportunities. Provided that the policy was a primary determinant of the biofuel industry's development, these economic studies' findings were then included in the debate on existing policy support for biofuels and biofuels' potential microalgae play an essential role in the policy background.